Answer:
(2x-7)(x+12)
Explanation:
2x²+17x-84
(2x )(x )
We were told to use 7 and 12 to equal 84. Let's try 12 in the first bracket and 7 in the second:
(2x 12)(x 7): (2x)(7) and (12)(x) = 14x and 12x, which we cant make 17x from
Now let's try 7 in the first bracket and 12 in the second:
(2x 7)(x 12): (2x)(12) and (7)(x) = 24x and 7x, which we CAN use to make 17x if the 7x is negative, ie place a '+' before the twelve in the second bracket and a '-' before the seven in the first bracket.
(2x-7)(x+12)
Double check: (2x-7)(x+12)=2x(x+12)-7(x+12)=2x²+24x-7x-84=2x²+17x-84